Product design: Impact of government policy and consumer preference on company profit and corporate social responsibility. (4th October 2018) - Zhang, Xiang; Zhang, Lei; Fung, Ka Yip; Rangaiah, Gade Pandu; Ng, Ka Ming
Highlights: Product development with the incorporation of government policy and corporate social responsibility. Classification of government policy and its influences on product development. Multi-objective optimization framework for business decision making. Solar photovoltaic case study demonstrates the application of the framework. Abstract: A multi-objective optimization framework that considers the influence of government policy on product design is presented. The government policy affects product design in the form of financial and non-financial incentives, and regulations. The consumers affect product design by their purchase behavior that is in turn influenced by price, product quality, and the presence of competing products. The company responds to these influencing factors to design a product with as high a profit as possible while satisfying corporate social responsibility. Different models as well as rule-based methods – quality, consumer utility, product demand, product cost, capital budgeting, social indices, and government policy – are presented. A solar photovoltaic case study is used to illustrate the framework.